2015
DOI: 10.1111/pde.12542
|View full text |Cite
|
Sign up to set email alerts
|

Topical Timolol Solution Versus Laser in Treatment of Infantile Hemangioma: A Comparative Study

Abstract: Lasers, 595-nm pulsed dye and 1,064-nm neodymiumdoped yttrium aluminum garnet (Nd:YAG), have been used successfully for the treatment of infantile hemangiomas (IHs). Recently the use of a topical b-blocker, specifically timolol maleate, has been promising in the treatment of IHs. The objective of this study was to compare the effectiveness of topical timolol 5 mg/mL solution with that of combined sequential dual-wavelength laser in the treatment of IHs. Sixty children with IHs were divided randomly into two eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 14 publications
1
26
0
Order By: Relevance
“…26,27 One study comparing ophthalmic timolol and imiquimod reported no differences in effects. 28 Two studies using laser as a comparator reported mixed results: no differences in average overall improvement in 1 study comparing timolol and timolol plus laser modalities 30 and greater response to timolol in superficial IH, with greater response of mixed IH to timolol plus laser in another. 29 In our network meta-analysis specifically, all noncontrol treatments were estimated to have a larger expected clearance than control arms.…”
Section: Figurementioning
confidence: 99%
See 4 more Smart Citations
“…26,27 One study comparing ophthalmic timolol and imiquimod reported no differences in effects. 28 Two studies using laser as a comparator reported mixed results: no differences in average overall improvement in 1 study comparing timolol and timolol plus laser modalities 30 and greater response to timolol in superficial IH, with greater response of mixed IH to timolol plus laser in another. 29 In our network meta-analysis specifically, all noncontrol treatments were estimated to have a larger expected clearance than control arms.…”
Section: Figurementioning
confidence: 99%
“…[19][20][21][22] One cohort study compared oral propranolol (2 mg/kg/day) and intralesional bleomycin (0.5 mg/kg) 23 ; and 1 RCT and 1 cohort study evaluated oral propranolol (2-3 mg/kg/day) and other β-blockers (1-4 mg/kg/ day). 24,25 Three cohort studies and 2 RCTs assessed topical timolol (0.5%) compared with placebo or observation or another agent, [26][27][28][29][30] and 1 RCT and 1 cohort study evaluated different steroids, including oral prednisone and intralesional triamcinolone. 31,32 Studies included a total of 1265 children with IH (ages ranging from 2 weeks to 9 years), and most were fair quality.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations